COMPLEX EVALUATION AND JUSTIFICATION BASED ON PHYSICAL-MECHANICAL PROPERTIES OF GASES - Ochilov, Tulkin Ashurovich; Mengnarov, Shuxrat Soatovich; Atanafasov, Muhiddin Rahmonovich; Ismoilov, Doniyorbek Abdulkhamidovich (Innovative Development in Educational Activities, 2024)
in this article, 5000 tex pelts were made on the JFA-226 carding machine at the production enterprise, 3 types of pelts were made on the HSR-1000 type pelting machine in the laboratory of TTESI under the "Spinning Technology" department, JAT of the Japanese company "Toyota" in the laboratory under the "Textile Fabric Technology" department On the 810 loom, yarn made of 100% cotton fibers was thrown into the warp thread, and yarn mixed with secondary fibers was thrown into the loom yarn.